2019
DOI: 10.3390/app9214629
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Changes of Urban Rainstorm-Related Micro-Blogging Activities in Response to Rainstorms: A Case Study in Beijing, China

Abstract: Natural disasters cause significant casualties and losses in urban areas every year. Further, the frequency and intensity of natural disasters have increased significantly over the past couple of decades in the context of global climate change. Understanding how urban dwellers learn about and response to a natural hazard is of great significance as more and more people migrate to cities. Social media has become one of the most essential communication platforms in the virtual space for users to share their know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Social media data collected through Twitter, Facebook, Flicker, and Weibo can be used to improve understanding of urban hydrology. Wang et al [10] examine rainstorm-related micro-blogging activities in response to rainstorms in an urban environment at fine spatial and temporal scales. The study collected hourly precipitation data and a total of 3.32 million Weibo blogs geotagged with Beijing, China from June to September 2017.…”
Section: Gis For Hydrologymentioning
confidence: 99%
“…Social media data collected through Twitter, Facebook, Flicker, and Weibo can be used to improve understanding of urban hydrology. Wang et al [10] examine rainstorm-related micro-blogging activities in response to rainstorms in an urban environment at fine spatial and temporal scales. The study collected hourly precipitation data and a total of 3.32 million Weibo blogs geotagged with Beijing, China from June to September 2017.…”
Section: Gis For Hydrologymentioning
confidence: 99%
“…The rise of big data from social media has significantly evolved the methods and focus of linguistic diversity research [24][25][26][27][28][29][30]. Blodgett, Green [31] used Twitter geolocation data to explore dialectal variations in African-American English.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most severe weather systems, a rainstorm triggered by the SWV is a complex and representative example of a typical rainstorm [3,4]. The SWV has played a crucial role in numerous significant precipitation events and floods, ranking as the second most important rainstorm system in China after typhoons [5,6]. Previous studies have found that there are significant differences in the precipitation distribution caused by the different movement paths of the SWV [7][8][9].…”
Section: Introductionmentioning
confidence: 99%